If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4(3c + -5) = -32 Reorder the terms: 4(-5 + 3c) = -32 (-5 * 4 + 3c * 4) = -32 (-20 + 12c) = -32 Solving -20 + 12c = -32 Solving for variable 'c'. Move all terms containing c to the left, all other terms to the right. Add '20' to each side of the equation. -20 + 20 + 12c = -32 + 20 Combine like terms: -20 + 20 = 0 0 + 12c = -32 + 20 12c = -32 + 20 Combine like terms: -32 + 20 = -12 12c = -12 Divide each side by '12'. c = -1 Simplifying c = -1
| 4(3c-5)=32 | | 7/-3=7/x | | 5(-5c+2)=35 | | 3=1/5k | | x*0.6=0.84 | | x+1.8=3.25 | | 4(-4a-3)=36 | | x-1.24=1.9 | | x+2.4=4.1 | | 4(x-7)=39 | | 6z-29=3z-8 | | 3(3x-3)y=32 | | 6c-17=3c-35 | | 9z-24=5z-8 | | 60=13m+a | | 4x+6=-x+36 | | logE=17.8 | | 6y-5x-5=6(xy)-5 | | (-3a-b)+(2a-5b)= | | 8888=500 | | 2-3y=px | | 18-Y=(-18) | | 10z-93=4z-45 | | 4g-11=13-2g | | 5a+6=3a+10 | | y-13=36 | | 3(4f-7)=-45 | | 10x^(1/3)-10x | | 8-5q=23 | | 5x+11=2x+38 | | -1+6c=11 | | -8+9c=10 |